Eudaldo Forment, Ser y persona. Publicacions Edicions Universitat de Barcelona, 1982, 464 pp - Sacchi, Mario Enrique (1990)
Fil: Sacchi, Mario Enrique. Armada Argentina. Escuela de Guerra Naval; Argentina